Financing of NCD Prevention in LMICs: Pakistan Case Study - Ammar Rashid; Rozina Khalid; Kassim Nishtar; Saba Amjad; Huma Tahir (Journal of the Pakistan Medical Association, 2026)
Objective: The objective of this study is to estimate spending on NCD prevention in Pakistan and identify the enablers, challenges and dynamics underpinning population level NCD prevention spending, with particular focus on tobacco use, harmful use of alcohol, unhealthy diets and physical inactivity. Methods: Primary and secondary data collection was used to examine processes and organizational contexts that shape the formulation of policy and financial frameworks for NCD prevention. The methodology was categorized into three tiers; an academic literature review, scrutiny and analysis of official policy documents and budgetary data on health and NCDs, and in-depth stakeholder interviews with key government officials leading NCD programmes. Government and government routed donor spending on population level prevention was gauged to estimate NCD prevention spending. Where possible, impact of prevention programmes on disease incidence and risk factors was gauged through available outcome indicators. Results: Noncommunicable diseases are now the predominant cause of mortality and morbidity in Pakistan, accounting for approximately 58% of total deaths. The leading risk factors for NCDs in Pakistan are tobacco use, unhealthy diet, physical inactivity, obesity and air pollution. Governance issues and insufficient investment in health have long been challenges for the health sector. Conclusion: Pakistan faces a massive NCD burden, which continues to grow with time. NCDs like Cardio vascular Diseases (CVDs), diabetes, hypertension and cancers are among the main causes of mortality and morbidity in the country and increasingly form the reason for much of health spending and hospitalizations. However, Pakistan’s health policy focus remains on communicable and nutritional defects, with almost no focus on population level prevention of NCDs. While federal and provincial governments have begun to act to formulate a consolidated NCD policy response in recent years, there is a lot of ground that still remains to be covered for Pakistan to respond adequately to its NCD epidemic. Keywords: Diseases, Tobacco, Incidence, Health, Policy, Diabetes